Differences in the degree of nutrition and body composition of boys and girls of pubertal age - Elvira Nikšić; Marko Joksimović; Edin Beganović; Novica Gardašević (IP Iermakov S.S., 2021)
Background and Study Aim. The nutritional status of children can be assessed on the basis of clinical examination, laboratory procedures and anthropometric measurements. Height and body weight are most often used to determine nutrition. Children and adolescents who are at risk of being overweight often also become obese adults. Material and Methods. The research was conducted on a sample of 136 students (67 boys and 69 girls), with an average age of 11.56 years. The aim of the study was to determine the degree and differences in the degree of nutrition and body composition in boys and girls of pubertal age. Results. Based on the obtained results, T-test for small independent samples, it was determined that there are no statistically significant differences between boys and girls, both in the degree of nutrition and body composition, estimated by 10 variables using bioelectric impedance InBody 720. Also, it was found that 19.70% of boys are obese, as well as 17.40% of girls. Cumulatively with the percentage of malnourished respondents, a total of 61.50% of boys were not normally fed, as were 37.70% of girls. The obtained results indicate the need for a more extensive review of the analysed segments and a significantly larger sample of respondents, in order to act preventively in the fight against obesity, as the leading epidemiological health problem of today. Conclusion. It is obvious that physical activity based on physical education classes is not sufficient or is not sufficiently represented to meet the challenges of the modern way of life of children.